2021
DOI: 10.1089/apc.2021.0079
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators Affecting the HIV Care Cascade for Migrant People Living with HIV in Organization for Economic Co-Operation and Development Countries: A Systematic Mixed Studies Review

Abstract: Migrants in countries affiliated with the Organization for Economic Co-operation and Development (OECD) have a higher risk of acquiring HIV, experience delayed HIV diagnosis, and have variable levels of engagement with HIV care and treatment when compared to native-born populations. A systematic mixed studies review was conducted to generate a multilevel understanding of the barriers and facilitators affecting HIV Care Cascade steps for migrant people living with HIV (MLWH) in OECD countries. Medline, Embase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 113 publications
(437 reference statements)
6
33
0
1
Order By: Relevance
“…Our study also reported several novel findings which have not been explored in previous studies involving MLHIV (8, 9). We found that the unavailability of HIV care services in the areas where they worked (e.g., plantation areas) and a lack of public transportation between workplaces and healthcare facilities created a significant barrier for some participants to access the services.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Our study also reported several novel findings which have not been explored in previous studies involving MLHIV (8, 9). We found that the unavailability of HIV care services in the areas where they worked (e.g., plantation areas) and a lack of public transportation between workplaces and healthcare facilities created a significant barrier for some participants to access the services.…”
Section: Discussionsupporting
confidence: 62%
“…Although stigma and discrimination were not specifically identified as a primary concern of the participants in this study, previous investigations have reported that stigma and discrimination were experienced by MLHIV as barriers that hampered their access to HIV care services (18, 20, 31, 48, 49). Our findings also identified that the mobile, transient nature of their work across districts made it difficult for them to access HIV care services, which has not been reported in previous studies with MLHIV (8, 9). It is apparent that to fully understand HIV care access procedures and systems in different areas requires intensive effort, which seemed challenging for participants in this study who faced language barriers and have limited knowledge and low levels of education.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…2,4 Numerous barriers affect PLWH's experiences and can delay any step of the cascade or lead to disengagement throughout HIV care. 2,[4][5][6] The linear approach to the cascade also disregards the pathways by which PLWH re-engage with care and treatment, for instance, after moving to a new jurisdiction. In summary, linearity may veil PLWH's actual narratives of disengagement, loss to follow-up, and re-engagement in care.…”
mentioning
confidence: 99%